PERAN DIVISI PASSANGER SERVICE HANDLING DALAM MELAYANI PENUMPANG PADA PT. JASA ANGKASA SEMESTA BANDAR UDARA INTERNASIONAL ADISUTJIPTO YOGYAKARTA - , M IDRIS HAKIM ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Role of Passenger service Handling Division in the Serving Passengers at PT. Jasa Angkasa Semesta Adisutjipto International Airport. Diploma Toursim Department Vocational Collage Gadjah Mada University Yogyakarta. This final project examines the role of passenger service handlingdivision in the serving passengers at PT. Jasa Angkasa Semesta Adisutjipto International Airport. This research aims to analyze the role of passenger service handling division to serve passengers in the PT. JAS Adisutjipto International Airport of Yogyakarta, To find how to process special passengers handling in the PT. JAS Adisutjipto International Airport, to find out any constraints faced by passenger service handling staffin the PT. JAS Adisutjipto International Airport. The methode used is descriptive methode with collection techniques of data such as direct observation in PT. JAS Adisutjipto International Airport of Yogyakarta, interview with informants that could provide information and the use of documents and literature studies to get the data required and then the data in the analysis. The results showed that the passenger service handling division has an important role to serve passengers when the pre â flight until post â flight, without the passengers service handling division, the airlines company can not provide maximal service to passengers when the daparture and arrival. The conclusion is the passenger service handling is very important role in the smooth operation of flight when in the aiport.